ENHANCING STUDENTS SPEAKING SKILL THROUGH OUTDOOR LEARNING METHOD AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF FOURTH SEMESTER STUDENTS KHAIRUN UNIVERSITY IN ACADEMIC YEAR 2022/2023 - Hamida A. Jasin; Muhammad Arif Wicaksono (Jurnal Bilingual, 2023)
This research entitled Enhancing Students' Speaking Skill through Outdoor Learning Method of Fourth Semester Students of English Language Education Study Program at Khairun University in Academic Year 2022/2023 is intended to find out the implementation of outdoor learning in teaching speaking skill, and to find out the enhancing of students' speaking skill through the implementation of outdoor learning. In this study the researcher uses action research because the researcher describes the data inform of words rather than numbers. The researcher uses functional text uses students of fourth semester of English Language Education Study Program as the data source of this research. The research instrument used by the writer is in the form of observation checklist, and test. The data is in the research are mainly gathered through the use of pre-test, observation, questionnaires, and post-tests. In analyzing the data, the researcher applies descriptive tehnique. After the data are collocted, they are analyze based on five indicators; fluency,pronunciation, grammar, vocabulary and accuracy in the functional text. The result shows that the implementation of outdoor learning method through three types pre-activity outdoor, while activity outdoor, and post-activity outdoor can improve the students' speaking skill. The implementation of outdoor learning method can improve the students' speaking skill of English language education study program at Khairun University in academic year 2022/2023. In the pre-test result, in which they formerly did not learn using outdoor learning methods , the mean of the pre-test was 58.02. After they learn English using outdoor learning method, the mean of post test was 70,8.